La mobilité contextuelle comme lien entre la mobilité quotidienne et la mobilité résidentielle. Du concept à la pratique - Nathalie Buchot (VertigO)
Living in one place also implies mobility. This hypothesis was developed over 15 years’ experience accompanying the underprivileged in housing issues and lies at the basis of the present study, which examines the effects, obstacles and levers involved in restricted residential mobility in residential neighborhoods of the National Agency for Urban Renewal (Agence Nationale de Rénovation Urbaine – ANRU) in Angers and Trélazé (France). Looking at our results in the light of contextual mobility, the close relationship between man and nature becomes apparent. Indeed, the cognitive process connecting mobility and residence can only take place within a reassuring and calming environment. On the other hand, living in degraded, depreciated social housing clearly hinders this process. The present study on forced relocation thus demonstrates the need for combining urban planning, social and environmental approaches in policymaking.